2018
DOI: 10.1038/gim.2017.102
|View full text |Cite
|
Sign up to set email alerts
|

The wide genetic landscape of clinical frontotemporal dementia: systematic combined sequencing of 121 consecutive subjects

Abstract: PurposeTo define the genetic spectrum and relative gene frequencies underlying clinical frontotemporal dementia (FTD).MethodsWe investigated the frequencies and mutations in neurodegenerative disease genes in 121 consecutive FTD subjects using an unbiased, combined sequencing approach, complemented by cerebrospinal fluid Aβ1-42 and serum progranulin measurements. Subjects were screened for C9orf72 repeat expansions, GRN and MAPT mutations, and, if negative, mutations in other neurodegenerative disease genes, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 43 publications
5
42
0
1
Order By: Relevance
“…Surprisingly, levels of p‐tau ant t‐tau were increased in all three, with decreased levels of Aβ42 only in one of them. Several previous reports have described diminished CSF Aβ levels in sporadic or/and genetic FTLD . It is discussed whether this finding is related to an increased deposition of Aβ spices or to a reduction of Aβ production, as it is associated with a reduction in soluble APP levels.…”
Section: Discussionmentioning
confidence: 86%
“…Surprisingly, levels of p‐tau ant t‐tau were increased in all three, with decreased levels of Aβ42 only in one of them. Several previous reports have described diminished CSF Aβ levels in sporadic or/and genetic FTLD . It is discussed whether this finding is related to an increased deposition of Aβ spices or to a reduction of Aβ production, as it is associated with a reduction in soluble APP levels.…”
Section: Discussionmentioning
confidence: 86%
“…Autosomal dominant inherited cases often occur clustered in families [ 13 ]. The large majority of sporadic FTLD cases is, however, of unknown etiology, albeit genetic alterations are to be expected there too [ 14 ]. The behavioural variant (bvFTD) accounts for more than half of the cases [ 15 ] and is histopathologically described by distinct inclusion bodies either comprised of Tau (FTLD-TAU) [ 16 ] or ubiquitinated TDP-43 (FTLD-TDP) [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The typical age‐of‐onset in these families is in the fifties, and patients show variable clinical presentation and disease duration (1–12 years). Sequencing studies identified several other CHCHD10 mutations in ALS/FTD cohorts, but lack functional characterization to support pathogenicity (Chaussenot et al , ; Dols‐Icardo et al , ; Zhang et al , ; Jiao et al , ; Zhou et al , ; Blauwendraat et al , ).…”
Section: Introductionmentioning
confidence: 99%